Effects of planting date on yield related traits of some soybean genotypes in Sennar state of the Sudan - Ngalamu, T.; Odra, J.; Ashraf, M.; Meseka, S.K. (2013)
Experiments were conducted at El Gantra farm in Sennar State, Sudan to verify the effects of sowing date on five soybean (Glycine max L. Merrill) genotypes planted at five different planting dates in 2009 and 2010. The objectives were to assess the performance of five soybean genotypes under different sowing dates and identify genotype(s) with high yield potential for release to local farmers in Sennar State. The trial was arranged as a split-plot design replicated three times, with planting date as main plot and genotype as subplot. The combined analysis of variance over two years showed significant effect (P<0.01) of sowing dates for all the measured traits, with the exception of number of seeds per pod and 100-seed weight in both years (2009 and 2010). The differential response of the genotypes to the different planting dates and the interaction effects were significant for all the traits evaluated except for plant height, first pod height, number of branches per plant, number of seeds per plant and 100-seed weight. Significantly higher grain or seed yield were obtained in 2010 with mean value of 0.79 t/ha compared with 0.69 t/ha in 2009. There was also no change in the trend of performance of genotypes across the five sowing dates in the two years. The highest seed yield of 1.2 t/ha was obtained from sowing carried out on 10th August in 2009, followed by that of 12th July (1.03 t/ha) and 26th July (0.93 t/ha) in 2010, which were the best of the five sowing dates in the two years. Thus, in order to achieve optimum productivity in soybean in Sennar State, it is recommended that planting of soybean should commence in early July. The best genotypes are TGx 1937-1F and TGx 1740-2F because they out yielded all other genotypes in the trials.